Technical Evaluation of Three Methods of Manual, Semi-mechanized, and Mechanized Peanut Harvesting in Moghan - J. Taghinazhad; S. Rahmani (Journal of Agricultural Machinery, 2023)
IntroductionThe harvesting stage is the most crucial phase in peanut production. In other words, one of the critical stages in producing this product is the harvest stage. Although it has its difficulties, this stage is associated with significant losses, which experts attribute to the high economic value of peanuts. In recent years, farmers in the Moghan Plain have also started considering this product due to the special conditions of the Iranian economy. In 2020, this study investigated three methods of peanut harvesting in two stages: manual, tractor-mounted thresher (semi-mechanized), and harvesting with a pull-type combine. The first stage involves the complete removal of the plants from the soil, while the second stage involves drying and separating the peanut pod from the plant in Moghan.Methods and MaterialsThe experiment followed a split-plot design in the form of randomized complete blocks with four replications. The main plot consisted of soil moisture levels at harvest time, which were tested at three different levels: a1- 21%, a2- 18%, and a3- 15%. The sub-plot involved testing the separation of peanut pods from the plant using three different methods: b1- combine harvesting, b2- harvesting with a tractor-mounted thresher, and b3- manual harvesting. The study evaluated important harvest indicators such as quantitative loss (first and second-stage losses), actual field capacity, harvest time, and the number of required laborers. The results led to the identification of the best harvesting system.Results and DiscussionThe study revealed that the optimal soil moisture content for the initial stage of harvest was 18%. For most parameters, there was a significant difference observed among treatments at the 1% level. The pull-type combine method had the highest farm capacity with a maximum of 0.46 ha per hour, while the manual harvesting method had the lowest capacity with a minimum of 0.006 ha per hour. The total losses ranged between 5.95% and 10.58%, with the manual harvesting method exhibiting the lowest loss and the pull-type combine method showing the highest loss. Furthermore, the manual harvesting method required more labor compared to the other methods.ConclusionBased on the obtained results, it is recommended to use a pull-type combine for the early harvesting of peanuts and a manual method for obtaining high-quality peanuts in the Moghan region.